2011
DOI: 10.1111/j.1365-2141.2011.08977.x
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models for studying pain in sickle disease: effects of strain, age, and acuteness

Abstract: Clinical management of severe pain associated with sickle cell disease (SCD) remains challenging. Development of optimal therapy would be facilitated by use of murine model(s) with varying degrees of sickling and pain tests that are most sensitive to vasoocclusion. We found that young (≤3 month old) NY1DD and S+SAntilles mice (having modest and moderate sickle phenotype, respectively) exhibit evidence of deep tissue/musculoskeletal pain. Deep tissue pain and cold sensitivity in S+SAntilles mice increased signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
141
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(155 citation statements)
references
References 33 publications
11
141
2
1
Order By: Relevance
“…3 We also found that cannabinoids mitigate chronic and hypoxia/reoxygenation (H/R)-evoked acute hyperalgesia in sickle mice. 4,5 Cannabinoids have anti-inflammatory effects and provide protection from ischemia/reperfusion injury. [6][7][8][9][10] Since pain is a manifestation of complex sickle pathobiology including inflammation, vascular dysfunction and ischemia/reperfusion injury, we investigated cannabinoid receptor-specific modulation of vascular function, inflammation and hyperalgesia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 We also found that cannabinoids mitigate chronic and hypoxia/reoxygenation (H/R)-evoked acute hyperalgesia in sickle mice. 4,5 Cannabinoids have anti-inflammatory effects and provide protection from ischemia/reperfusion injury. [6][7][8][9][10] Since pain is a manifestation of complex sickle pathobiology including inflammation, vascular dysfunction and ischemia/reperfusion injury, we investigated cannabinoid receptor-specific modulation of vascular function, inflammation and hyperalgesia.…”
Section: Introductionmentioning
confidence: 99%
“…19 Since vascular dysfunction, ischemia/reperfu-sion injury and inflammation are hallmark features of SCA, we hypothesized that targeting specific cannaboid receptors may have beneficial effects on sickle pathobiology and pain. We used transgenic HbSS-BERK mice, hereafter referred to as sickle mice, which show features of pain and inflammation similar to patients with SCA, 4,5,20 and sickle mice with deletion of CB2R, to examine the contribution of each cannaboid receptor in mast cell activation, neurogenic inflammation, and pain.…”
Section: Introductionmentioning
confidence: 99%
“…Control SCD mice (HBAA) are also available, in which only human α-and normal human β-globin alleles are expressed. [40,42] The phenotypes in SCD mice are highly similar to those observed in SCD patients. Both Berkley (HBSS-BERK) and Townes (HBSS) SCD mice display many of the pathophysiological changes observed in SCD patients including anemia, organ damage, hypoxia-induced cell sickling, and pain sensitivity.…”
Section: Animal Models Of Scd-associated Painmentioning
confidence: 65%
“…[40] Two common mouse models of SCD are the Berkeley [41] and Townes [42] models. In both of these models, the mouse α-and β-globin alleles have been knocked down, and human α-and human sickle β-globin alleles have been inserted.…”
Section: Animal Models Of Scd-associated Painmentioning
confidence: 99%
See 1 more Smart Citation